Perceptions of health care workers regarding the need for palliative care services in three selected hospitals in Lesotho - Mwabury, Tonny Abdul (Department of Medicine, 2022)
Background: In the last few decades, the increasing upsurge in HIV/AIDS and noncommunicable diseases such as heart disease, stroke and cancer as well as aging populations has given rise to the need for PC services in many countries globally, including Lesotho. However, available literature indicates gaps in PC development and integration in Lesotho. Aim: To explore the perceptions of health care workers regarding the need for PC services in three selected hospitals in Lesotho, with regards to knowledge of PC, the burden of care (especially to healthcare workers), existing PC services and policies which guide availability and access to PC medications. Objectives: (1) To explore selected health care workers' views on the burden of disease at the hospitals where they work and in Lesotho; (2) To identify knowledge, attitudes and beliefs on PC and linking that to the need for PC provision for patients diagnosed with life threatening conditions; including their families; (3) To determine which conditions in the HCWs' views qualify a patient to receive PC, and (4) To identify whether in the HCWs' views there is adequate development and provision of PC services in the hospitals where they work. Method: This study used a descriptive research design conducted within a qualitative approach. Individual semi-structured interviews were conducted with 12 research participants in three hospitals in Lesotho. Research participants included medical doctors, pharmacists, social workers and nurses. Data was recorded, transcribed verbatim and analyzed using thematic analysis. Results: Themes and sub-themes emerged from the data analysis: prevalent palliative care conditions, psycho-social support, referral criteria for palliative care services, palliative care challenges, poor infrastructure and lack of resources, accessibility and affordability of pain medication, and lack of palliative care policies and procedures. Conclusion: Although each hospital had a different pattern of views and challenges, the same reasons and issues were raised all of which suggests primarily that PC services were at low levels of operation, mostly unorganized and in many instances non-existent in Lesotho. The followings recommendations were presented: 1. Introduction of compulsory entry point education and Continuing Professional Development (CPD) for HCWs 2. Sensitization and advocacy for PC. 3. Adequate funding 4. Availability and accessibility of PC medications and 5. Policies promoting restrictions on prescriptions should be reviewed towards formulation new policies.